Analytical approach for force-displacement behavior of deformed reinforcing bars embedded in concrete. (15th June 2023) - Kong, De-Yang; Liew, J.Y. Richard; Li, Shan
Highlights: An analytical approach is proposed to predict the force-displacement relationship of deformed reinforcing bar embedded in concrete. An equation is proposed for bond characteristics in post-yield range of reinforcing bars. The approach is applied for progressive collapse analysis of composite beam-column joint subassemblies. Abstract: Component-based joint model suggested by Eurocode is a simple yet efficient approach to evaluating the joint behavior of composite beam-column subassemblies. The reinforcing bars in this approach play an instrumental role, especially for progressive collapse analysis where the ultimate resistances and structural ductility of beam-column subassemblies are significantly influenced and in some extreme cases directly governed by the reinforcing bars. This paper describes an analytical approach for predicting the force-displacement characteristics of deformed reinforcing bars that are embedded in concrete blocks. In contrast to previous studies that roughly predefined the profiles of bar and bond stresses in tension, this paper utilizes an iteration method to provide a more accurate and simpler description of such non-uniform local behavior. This approach has greater flexibility to account for the variations in the embedment length of reinforcing bars, lateral restraints and failure modes. The proposed approach is verified using four groups of published reinforcing bar pull-out tests. The predicted force-displacement relationships, distributions of local slips, bond stresses, and bar stresses along the length are shown in reasonable agreement with the test results. Finally, component-based joint models are established for composite beam-column subassemblies under progressive collapse scenarios, in which the force-displacement relationships of the reinforcing bar components are determined through the proposed approach.